Transmitted Drug Resistance Mutations and Subtype Diversity among Hiv-1 Sero-Positive Voluntary Blood Donors in Accra, Ghana - Obeng, B. M. (University of Ghana, 2017)
Detection of HIV-1 transmitted drug resistance (TDR) and subtype diversity (SD) are public health strategies to assess current HIV-1 regimen and ensure effective therapeutic outcomes of ART among HIV-1 patients. Globally, limited data exist on transmitted drug resistance and subtype diversity among blood donors. In this study, drug resistance mutations and subtype diversity among HIV-1 sero-positive blood donors in Accra, Ghana was characterized. Methods Purposive sampling method was used to collect 81 blood samples from the Southern Area Blood Center, Korle-Bu that tested positive for HIV using the HIV Ag/Ab 4th gen (Fortress Diagnostics, U.K). Serology was used to confirm and discriminate between the presence of HIV-1 and HIV-2 antibodies in all samples using INNO-LIA HIV I/II score (Fujirebio, Belgium). Viral RNA was then extracted using QIAamp viral RNA Mini Kit (QIAGEN, Germany) from plasma samples confirmed as HIV-1 positive. Reverse transcription polymerase chain reaction (RT-PCR) was used to amplify the reverse transcriptase (RT) and protease (PR) genes of HIV-1 using Transcriptor High Fidelity cDNA synthesis kit for the reverse transcriptase (RT) step and Expand High Fidelity PCR System for the PCR step (Roche Diagnostics, Germany). Agarose gel electrophoresis was used to ascertain the presence of expected amplification products. The expected products were purified and cycle sequenced using BigDye Terminator v3.1 cycle sequencing kit (Applied Biosystems, U.S.A). Sequences were read out using the ABI genetic analyzer 3130xl (Hitachi, Japan) and data analyzed for drug resistance mutations and HIV-1 University of Ghana http://ugspace.ug.edu.gh xiv subtypes using the Stanford University HIV drug resistance database and Los Alamos HIV database respectively. Results Out of the 81 plasma samples collected, 61 (75%) were confirmed as HIV-1 sero-positive by INNO-LIA HIVI/II Score kit with no HIV-2 and dual HIV-1/2 infections. The remaining samples (25%) were confirmed as HIV sero-negative. Of the 61 confirmed positive samples, 53% and 50% were successfully amplified in the RT and PR genes respectively. Nucleotide sequencing of amplified samples revealed the presence of major drug resistance mutations in two (2) samples; E138A in one sample and another with K65R. HIV-1 Subtypes including subtypes A, B, CRF02_AG and CRF09_cpx were found. Conclusion This study has found major drug resistance mutations, E138A and K65R in the RT gene that confer high level resistance to most NNRTIs and NRTI respectively. CRF02_AG was most predominant, the recorded percentage of subtype B and the evolutionary relationship inferred by phylogenetic analysis suggest possible subtype importation. The data will inform the selection of drugs for ART initiation to maximize therapeutic options in drug-naïve HIV-1 patients in Ghana.
Keywords: HIV-1 transmitted drug resistance (TDR); subtype diversity (SD); public health strategies; ffective therapeutic outcomes; HIV-1 sero-positive blood donors; Agarose gel electrophoresis; BigDye Terminator v3.1 cycle sequencing kit; drug resistance mutations